COMPARAÇÃO DE MÉTODOS DE CUBAGEM PARA EUCALIPTO - SOUZA, Hudson Santos; DRESCHER, Ronaldo; VENDRUSCOLO, Diogo Guido Streck; MOURA, Jhonny Pinto Vieira Mendes; SIQUEIRA, Tiago Altobelle da Silva; MAMORÉ, Fernanda Meyer Dotto (Brazilian Journal of Biometrics, 2017)
Calculation of timber volume in eucalyptus stands has fundamental importance for the monitoring and planning of commercial plantations. Thus, the aim of the study was to compare scaling methods for Eucalyptus urograndis. The survey was conducted on a farm in Itiquira, southeast region of the state of Mato Grosso, Brazil. The settlement of eucalyptus is 4 years old, and the genetic material it’s from Eucalyptus urophylla × grandis hybrid at a spacing of 3m×3m. The data were collected from permanent plots randomly distributed in the population, with a sampling intensity of a portion of every three hectares. The plots were circular with an area of 400 m². They were scaled 36 trees by Newton's method, and measured the d0,1 (diameter of 0.1 m above the ground), Diameter at Breast Height (1.3 m height) and from the DBH every 2 m to a minimum diameter of 1 cm. In addition to the scaling by Newton, it was tested six methods, namely: Huber, Smalian, Hohenadl, FAO, Pressler and Centroid. The methods of Huber, FAO, Pressler and Centroid had a slight tendency to underestimate the mean volume of trees, especially the Pressler method, while the Smalian Hohenadl method had a slight tendency to overestimate the volume of trees. According to the results of this research, there is no statistical difference between the scaling methods evaluated.